An unusual phenomenon of recurrent aortic dissection with hypertension: a rare case report - Atthoriq Hayat Kurnia; Verry Gunawan Sohan (Journal of Indonesia Vascular Access, 2023)
Introduction: Recurrent aortic dissection is a rare and challenging phenomenon for cardiovascular cases in the world. In the last two decades among patients with initial aortic dissection, only 5% have become recurrent aortic dissection, typically seen in patients with connective tissue disorders. We report an unusual case of recurrent aortic dissection with hypertension. Case Presentation: A 55-year-old female came with complaints of chest pain from the mid and left chest to the back. The symptoms had occurred for almost three years after treatment and post-surgery of her prior aortic aneurysm dissection. But she still had the same signs and symptoms as before. We requested thoracoabdominal CT angiography to confirm the diagnosis. A thoracoabdominal CTA shows recurrent aortic dissection, because of its difficulty and rarity we need proper consideration. For now, we prefer conservative medical treatment with management of blood pressure and pain control, also treatment for other diseases. Conclusion: Recurrent aortic dissection is still a special challenge for physicians and a rare extreme phenomenon that may need a special approach and more complex treatment strategies.